2019
DOI: 10.3748/wjg.v25.i27.3503
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophils in the gastrointestinal tract and their role in the pathogenesis of major colorectal disorders

Abstract: Eosinophils are currently regarded as versatile mobile cells controlling and regulating multiple biological pathways and responses in health and disease. These cells store in their specific granules numerous biologically active substances (cytotoxic cationic proteins, cytokines, growth factors, chemokines, enzymes) ready for rapid release. The human gut is the main destination of eosinophils that are produced and matured in the bone marrow and then transferred to target tissues through the circulation. In heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 247 publications
(311 reference statements)
7
55
0
2
Order By: Relevance
“…Treatment with DSS caused injury to the mucous membrane and eosinophil infiltration of the colonic mucosa. Eosinophils have been shown to be closely associated with IBD . On histology, KST prevented the colon mucosa atrophy and eosinophil infiltration of the colon caused by DSS.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with DSS caused injury to the mucous membrane and eosinophil infiltration of the colonic mucosa. Eosinophils have been shown to be closely associated with IBD . On histology, KST prevented the colon mucosa atrophy and eosinophil infiltration of the colon caused by DSS.…”
Section: Discussionmentioning
confidence: 99%
“…Eosinophil infiltration is considered unfavorable in Hodgkin's lymphoma, but positive in breast and 469 prostate cancers 126 . As recently reviewed 127 , higher numbers of infiltrating eosinophils detected in 470 CRC growth inhibition remain poorly understood. 472…”
Section: Statistical Analysis Of the Association Between Tissue Micromentioning
confidence: 99%
“…In addition, the study showed deformations of the auditorium ceiling. The basics of structure deformation monitoring methods in conjunction with 3D modeling technologies are described in the works [22][23][24].The results of the laser scanning were used for building the geometry of the auditorium and its ceiling.…”
Section: Fig4 Comparison Of the Cloud Of Points And The Informationmentioning
confidence: 99%